Changing ophthalmic practice during the COVID-19 pandemic in Uganda - Rizwan Kanji, Raheel; Arunga, Simon (Community Eye Health, 2020)
Mbarara University and Referral Hospital Eye Centre (MURHEC) is a governmentowned tertiary referral eye unit that provides eye care to the South Western part of Uganda, providing over 10,000 consultations per year. It also offers residency training in ophthalmology and currently has 20 residents.
Keywords: Ophthalmic practice; COVID-19 pandemic